Nurses’ perceptions of providing psychosexual care for women undergoing gynaecological cancer treatment - Williams, Natalie Fleur (Curtin University, 2018)
Gynaecological cancer presents challenges to women’s sexuality. Using qualitative description, interviews were analysed gaining insight into how seventeen Western Australian nurses conceptualise provision of psychosexual care for women undergoing gynaecological cancer treatment. Five themes and nine subthemes were revealed and views differed around whether factors had a positive or negative impact on care. Nurse-patient rapport, making assumptions and role clarification were discussed. Recommendations include standardised psychosexual assessment, shared responsibility of care, and skills-based education programs.